Comparing the Effectiveness of Human and AI-Generated Endorsers in Advertising Campaigns - Akbari, Deni Adha; Sumarwan, Ujang; Hasanah, Nur; Edison, Rizki Edmi (Agregat: Jurnal Ekonomi dan Bisnis, 2023)
This review explores the contrasting roles of machine-driven and human endorsers in advertising campaigns, assessing their ability to engage consumer visual attention. With its ability to tailor content and predict consumer responses, the machine-driven approach has brought new dimensions to advertising, though its influence may differ across various demographic groups. Conversely, human endorsers substantially impact consumer decisions because they can form emotional bonds, enhance authenticity, and build trust. The review encourages a perspective that sees machine-driven and human endorsers not as rivals but as complementary forces, with further studies needed to investigate how to combine these elements best.